Evaluation of the Energy Performance of the Amougdoul Wind Farm, Morocco - Asma Ezzaidi; Mustapha Elyaqouti; Lahoussine Bouhouch; Ahmed Ihlal (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper is concerned with the assessment of the the performance of the Amougdoul wind farm. We have determined the Weibull parameters; namely the scale parameter, c (m/s) and shape parameter, k. After that, we have estimated energy output by a wind turbine using two techniques: the useful power calculation method and the method based on the modeling of the power curve, which is respectively 134.5 kW and 194.19 KW corresponding to 27% and 39% of the available wind energy, which confirm that the conversion efficiency does not exceed 40%.